Coping skills among Malaysian armed forces paratrooper trainees - Normah Che Din,; Shahidah Leong Abdullah,; Fauziah Shaari, (penerbit ukm, 2003)
This study was carried out to investigate coping process in relation to specific distressful episodes xperienced by 120 paratrooper trainees. Scores of direct coping and emotional coping that were derived from the “Ways of Coping questionnaire were analyzed to examine the role of appraisal, level of anxiety, depression and level of stress as predictors of coping. Extrovert personality did not influence direct or emotional coping at all three phases (Training, Outdoor, and Jumping phases), Neurotic personality influenced direct coping in phases II and emotional coping in phase III. Anxiety affects emotional and direct coping in phases II and III. Depression significantly influenced emotional and direct coping at phase I only. Stress has significant contribution toward emotional and direct coping for all three phases. Appraisal signifantly affects direct coping at all phases but only phase I and II for emotional coping